2020
DOI: 10.1039/d0na00049c
|View full text |Cite
|
Sign up to set email alerts
|

Optical writing and single molecule reading of photoactivatable and silver nanoparticle-enhanced fluorescence

Abstract: We present a hybrid nano-molecular system for optically activated, silver nanoparticle enhanced fluorescence in solution and in thin-polymer films, alongside single molecule level insights into the metal-enhanced fluorescence mechanism.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(74 citation statements)
references
References 59 publications
1
60
0
Order By: Relevance
“…We recently reported a hybrid nanomolecular system for applications of fluorescence activation in solution and in thin polymer films . In brief, the highly quenched emission of boron dipyrromethene (BODIPY) species 1 can be turned on by optically stimulating a ligand exchange around the boron center using either UVA- or UVC-activated photoacid generators (PAGs) to form species 2 (Chart ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported a hybrid nanomolecular system for applications of fluorescence activation in solution and in thin polymer films . In brief, the highly quenched emission of boron dipyrromethene (BODIPY) species 1 can be turned on by optically stimulating a ligand exchange around the boron center using either UVA- or UVC-activated photoacid generators (PAGs) to form species 2 (Chart ).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported a hybrid nanomolecular system for applications of fluorescence activation in solution and in thin polymer films. 30 In brief, the highly quenched emission of boron dipyrromethene (BODIPY) species 1 can be turned on by optically stimulating a ligand exchange around the boron center using either UVA-or UVC-activated photoacid generators (PAGs) to form species 2 (Chart 1). We further established that triangular silver nanoparticles (AgNP) with a 104 ± 28 nm edge length (Figure S1) dramatically increase the steady-state fluorescence intensities of 1 and 2 through metalenhanced fluorescence (MEF) in thin films.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1B, green traces). Previously, we demonstrated that the fluorescence of green-emitting probes based on the BODIPY platform can experience MEF by large triangular silver nanoplates (∼ 80 nm), for which the surface plasmon band is centred at 660 nm (Dogantzis et al, 2020; Golian et al, 2021; Hodgson et al, 2020). Indeed, large, non-spherical nanoparticles are known to exhibit increased scattering (Knoblauch et al, 2020; Lakowicz, 2005; Lakowicz et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…For example, optical writing and single-molecule reading of photoactivatable and silver nanoparticle enhanced fluorescence could be mentioned. 115 In this approach a hybrid nanoparticle-molecular system was developed, formed by silver nanoparticles and a fluorogenic boron dipyrromethene (BODIPY) that is selectively activated by UVA or UVC light in the presence of a targeted photoacid generator. In this manner accurate single-molecule readings were achieved in the near surrounding of the plasmonic structure.…”
Section: Perspectives Towards Biosensing and Single Molecule Detectio...mentioning
confidence: 99%